2004
DOI: 10.1194/jlr.m300450-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Raising HDL cholesterol without inducing hepatic steatosis and hypertriglyceridemia by a selective LXR modulator

Abstract: Liver X receptors (LXRs) are ligand-activated transcription factors that belong to the nuclear receptor superfamily. LXRs activate transcription of a spectrum of genes that regulate reverse cholesterol transport, including the ATP binding cassette transporter A1 (ABCA1), and raise HDL cholesterol (HDL-C) levels. However, LXR agonists also induce genes that stimulate lipogenesis, including the sterol response element binding protein (SREBP1-c) and fatty acid synthetase (FAS). The induction of these genes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 27 publications
12
117
0
2
Order By: Relevance
“…GW3965, another synthetic LXR ligand, can inhibit the development of atherosclerosis in both LDLR Ϫ/Ϫ and apoE Ϫ/Ϫ mice. It has no effect on lipogenesis in both wild-type and LDLR Ϫ/Ϫ mice, but not in apoE Ϫ/Ϫ mice (21,47). The reduced side effects may be due to the fact that GW3965 is a weak activator of LXR rather than it has a higher selectivity for LXR␤ than LXR␣ (47).…”
Section: Discussionmentioning
confidence: 98%
“…GW3965, another synthetic LXR ligand, can inhibit the development of atherosclerosis in both LDLR Ϫ/Ϫ and apoE Ϫ/Ϫ mice. It has no effect on lipogenesis in both wild-type and LDLR Ϫ/Ϫ mice, but not in apoE Ϫ/Ϫ mice (21,47). The reduced side effects may be due to the fact that GW3965 is a weak activator of LXR rather than it has a higher selectivity for LXR␤ than LXR␣ (47).…”
Section: Discussionmentioning
confidence: 98%
“…Many investigators used T0901317 at 50 mg/kg per day and observed lipogenic effects in previous studies. [44][45][46][47][48] To avoid severe hepatic lipogenesis, we used a comparatively low dose (10 mg/kg per day) in this study. Recently, T0901317 and a new steroidal LXR agonist, DMHCA, were reported to decrease the activity of intestinal and renal sodium gradientdependent phosphate transporters, and the gene expressions of lipogenic enzymes with DMHCA were lower than those gene expressions after activation by T0901317.…”
Section: Discussionmentioning
confidence: 99%
“…LXR target genes include those that express proteins involved in the efflux of cholesterol from the cell (155,157,174,189) as well as bile acid synthesis (174) and lipogenesis (174). Thus, global LXR activation by synthetic agonists has a plethora of effects, including elevated high-density lipoprotein (HDL) levels (25,28,98,126,147,163,178), hypertriglyceridemia (156,163), hepatic steatosis (65), increased excretion of cholesterol in bile (147,201), reduced efficiency of cholesterol absorption from the intestine (103,157,159,191,206), and increased loss of neutral sterols in feces (201).…”
Section: Cholesterolmentioning
confidence: 99%